2020
DOI: 10.1111/evo.14093
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of chain migration in an aerial insectivorous bird, the common swift Apus apus

Abstract: Spectacular long-distance migration has evolved repeatedly in animals enabling exploration of resources separated in time and space. In birds, these patterns are largely driven by seasonality, cost of migration, and asymmetries in competition leading most often to leapfrog migration, where northern breeding populations winter furthest to the south. Here, we show that the highly aerial common swift Apus apus, spending the nonbreeding period on the wing, instead exhibits a rarely found chain migration pattern, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
2
29
1
Order By: Relevance
“…Red‐backed shrikes are among the latest arriving migratory bird species in Europe during spring and thus, one could argue that the general late arrival may be responsible for the mismatch with local vegetation greenness. However, a recent study on swifts (another late arriving species in Europe) have shown a clear difference in timing of arrival with southern populations arriving earlier than northern populations (Åkesson et al 2020). Another possibility is that there is no, or only insignificant penalties on fitness of late breeding attempts across red‐backed shrike populations.…”
Section: Discussionmentioning
confidence: 99%
“…Red‐backed shrikes are among the latest arriving migratory bird species in Europe during spring and thus, one could argue that the general late arrival may be responsible for the mismatch with local vegetation greenness. However, a recent study on swifts (another late arriving species in Europe) have shown a clear difference in timing of arrival with southern populations arriving earlier than northern populations (Åkesson et al 2020). Another possibility is that there is no, or only insignificant penalties on fitness of late breeding attempts across red‐backed shrike populations.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it allows comparisons of results generated with other packages in similar principals [ 19 , 21 , 37 ]. We set the threshold to 2 for log-transformed light-level data to identify the twilight events (dawn-sunrise and sunset-dusk) minimizing the latitude variation around the equinox [ 19 , 20 , 22 ]. In the pre-analysis, we found that the swifts stayed in the breeding site for a very short and variable period before and after breeding.…”
Section: Methodsmentioning
confidence: 99%
“…This may well be the case for the Common Swift. A recent study revealed that the northern population of nominate apus winters in west and central sub-Saharan Africa, whereas the southern European apus swifts spend winters in contiguous regions of central and southeastern Africa [ 22 ]. It suggests that, even within the European breeding populations of the nominate apus , there are substantial spatiotemporal separation in wintering grounds, as well as migratory phenology [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common swift Apus apus often faces cold periods at their breeding sites, which span across Europe and beyond the Arctic Circle [24][25][26]. Anecdotally, it was reported that free-living breeding common swifts enter a nocturnal torpid state during harsh weather conditions which lower the activity of airborne insects for several days ( personal observation by J.R., [27,28]).…”
Section: Introductionmentioning
confidence: 99%